Evaluación del saneamiento físico legal y propuestas de medidas de mitigación de los barrancos de la ciudad de Moyobamba - Trigozo Suarez, Cesar Alonso (2016)
In this thesis work seeks to make an assessment of the current situation of the Ravines of Moyobamba, in regards basically to legal physical cleaning of these natural ecosystems also makes a proposal of sorne mitigation measures to be implemented to improve the management and handling of the ravines of Moyobamba, the same constitutes a natural attraction found in the urban and peri-urban part of town of Moyobamba, due to the implementation of a large number of activities that have 1 been implemented years after year the construction works in the different canyons of the city ofMoyobamba. The municipal current administration has every interest to address issues related to the development of basic infrastructure Urbana, in that sense, I urge me to have to do this research for the purpose of improving the road and pedestrian townscape on the ravines of the urban area city and on time of gradually improving walkability with different areas of your city ara able to connect with the city center, it helps improve the conditions of major life often make use of these services in urban spaces and green areas and visiting natural ecosystems such as the Ravines. The purpose of this research is to develop assessment for the land and proposed mitigation measures Ravines of Moyobamba, also, can handle appropriately the negative impacts potential products of daily activities that may be generated in these natural ecosystems. It is important to begin to visualize more seriously the public need for urban canyons and natural ecosystems that are properly sanitized and provide additional services such as the enhancement of these areas.